Fabrikasi dan uji kinerja mesin produksi santan terintegrasi pemarutan tipe sentrifugal kapasitas 10 liter/jam - Herdi Susanto; Darwin Hendri; Zakir Husin; Sulaiman Ali (Jurnal POLIMESIN, 2020)
The development of coconut processing technology to produce coconut milk for small and medium industry until now still uses a separate processing machine between coconut grating and coconut squeezing, so it is considered ineffective and less efficient. Therefore, previous studies aimed at improving the performance of coconut processing machines into coconut milk, have been carried out with the design of coconut milk producing machines that are integrated between the coconut grating process and the coconut milk squeezing process utilizing centrifugal force. Research aims to manufacture, a functional test of the machine components, and a calculation of the production cost per unit of the machine. The results showed that the coconut milk production machine has a power of 0.75 Kw, a maximum shaft rotation of 2850 rpm and an engine dimension of 600 x 600 x 1200 mm. The capacity of coconut milk production machines is 10 liters per hour, visual test results show that coconut milk production machines can function well at 1000 rpm, 1500 rpm, 2000 rpm and 2500 rpm. The total production cost for a unit of centrifugal coconut milk production machine with a production capacity of 10 liters per hour is Rp. 4,760,000.